The indigenisation of eco-theology: The case of the Lamba people of the Copperbelt in Zambia - Chibuye, Lackson (HTS teologiese studies, 2020)
This article shows how eco-theology could and should be indigenised in an African context using the Copperbelt in Zambia as a case study. The ecological crisis worldwide has given rise to the call for everyone to work together to start caring about our natural environment. In theology, the response to this call received the name eco-theology. By means of a literature review, ethnographic information and governmental legislation, the article tries to illustrate how eco-theology could and should be indigenised in an African context using the Copperbelt in Zambia as a case study. This article makes an attempt to contribute to the needed ecological renewal by reinterpreting two traditions that inform thinking on the Copperbelt: Christianity and African traditional religion. The supernatural belief of the Lamba people is no longer embodied in this creation, and it is not too late for the people to form any indigenous environmental protection movement to protect the sacredness of mother Earth from further contamination and exploitation by strengthening, maintaining and respecting the traditional teachings and the cultural laws. Obedience to God’s command to tend creation is a quest for continued creation by humans, so that value is added to what is already in existence. This is embodied making the place we live in more beautiful, appealing and peaceful. Fruitfulness with sustainability becomes core values for interdependence and earth keeping.Contribution: We wish to address the ecological situation of the mining industry in Zambia from a theological perspective by assessing the impact of the copper mining and processing industry on humans, their environment and nature and by showing how the traditions of African traditional religion (ATR) thought can be transformed into tools to oppose this ecological disaster.